Association Between a Novel Metabolic Score for Insulin Resistance and Mortality in People With Diabetes - Wang, Zhenwei; Xie, Jing; Wang, Junjie; Feng, Wei; Liu, Naifeng; Liu, Yun (Frontiers in Cardiovascular Medicine, 2022)
Background: Growing studies have shown that insulin resistance (IR) is associated with poor prognoses among patients with diabetes, whlie the association between IR and mortality has not been determined. Hence we aimed to evaluate the associations between IR and all-cause, cardiovascular diseases (CVDs) and cancer-related mortality in patients with diabetes. Methods: We enrolled 2,542 participants with diabetes with average age of 57.12 ± 0.39 years and 52.8% men from the 1999-2014 National Health and Nutrition Examination Survey. A novel metabolic score for insulin resistance (METS-IR) was considered as alternative markers of IR. Mortality data were obtained from the National Death Index records and all participants were followed up until December 31, 2015. Cox proportional hazards regression, restricted cubic spline and Kaplan-Meier survival curves were performed to evaluate the associations between METS-IR and all-cause and cause-specific mortality in patients with diabetes. Results: During 17,750 person-years of follow-up, 562 deaths were documented, including 133 CVDs-related deaths and 90 cancer-related deaths. Multivariate Cox regression showed that compared with Quintile 1 (METS-IR ≤ 41), METS-IR in Quintile 2, 3 and 4 was associated with all-cause mortality (Q2 vs Q1: HR 0.65, 95% CI 0.49-0.87, P = 0.004; Q3 vs Q1: HR 0.69, 95% CI 0.50-0.96, P = 0.029; Q4 vs Q1: HR 0.57, 95% CI 0.36-0.91, P = 0.019; respectively). Restricted cubic spline indicated that METS-IR was nonlinearly associated with all-cause and CVDs-related mortality. Threshold effect analyses determined that threshold values of METS-IR for all-cause and CVDs-related mortality were both 33.33. Only METS-IR below the threshold was negatively associated with all-cause and CVDs-related mortality (HR 0.785, 95% CI 0.724-0.850, P < 0.001; HR 0.722, 95% CI 0.654-0.797, P < 0.001; respectively). Subgroup analyses indicated that for all-cause mortality, the results were still stable in all subgroups except newly diagnosed diabetes, while for CVDs-related mortality, the association persisted only in participants who were ≤ 65 years, male, White, non-White, diabetes, or uesd oral drugs, insulin, insulin sensitizing drugs. Conclusions: METS-IR was nonlinearly associated with all-cause and CVDs-related mortality in patients with diabetes, and METS-IR below the threshold was negatively associated with all-cause and CVDs-related mortality.